The peculiarity of malvidin 3-O-(6-O-p-coumaroyl) glucoside aggregation. Intra and intermolecular interactions - Mendoza, Johan (2022)
UIDB/50006/2020 PTDC/QUI-OUT/29013/2017 MEX/Ref. 288188 SFRH/BD/143309/2019 IF/00225/2015 IF/01355/2014 CEECIND/00466/2017 REQUIMTE/EEC2018/PTDC/QUI-OUT/29925/2017